Serological Survey of Brucellosis in Slaughtered Local Chickens,Guinea Fowls, Ducks and Turkey in North-Eastern Nigeria - Adamu, N.B.; Adamu , S.G.; Jajere, M.S.; Atsanda, N.N.; Mustapha, F.B.; Maina, M. (International Journal of Poultry Science, 2014)
Serological survey to determine Brucella infection in traditionally managed local chickens, guinea fowl, ducks and turkey in Borno State was conducted using Rose Bengal Plate Test (RBPT) and Microtitre Agglutination Test (MAT). Out of 556 sera from local chicken, 84 from guinea fowls, 50 from ducks and 40 from turkey were examined, the seroprevalence of rates of 10(1.8%), 6(7.1%), 2(5.0%) and zero were obtained from the local chicken, guinea fowl, duck and turkey, respectively by RBPT. While MAT recorded 13(2.3%), 8(9.5%) and 3(6.0%) from local chickens, guinea fowl and duck, respectively. Brucellosis is present in local chickens, guinea fowl and turkey which may serve as source of infection to livestock and humans. Public education and enlightenment campaign to poultry handlers on the dangers, there is need for a large scale epidemiological investigation of the disease in chickens.